Analysis of the Living Standards of Fishing Families in the Hook-and-Line Fishing Industry Based on Women's Empowerment in Tateli Village - Manoppo, Victoria E. N.; Durand, Swenekhe S.; Aling, Djuwita R. R. (Sam Ratulangi University, 2025)
The specific objectives of this study are: Identifying and carefully explaining the standard of living of fishing families based on women's empowerment/housewives in Tateli Dua Village, Mandolang District, Minahasa Regency. 1. The method used in this study is the census method. 2 Data Collection Techniques Data collected through two sources, namely primary data and secondary data. Primary data is data that is directly obtained through direct interviews at the research location, filling out questionnaires. 3 Data Analysis Methods Analysis of research data results is divided into two types, namely quantitative analysis and qualitative analysis. Engel Index Analysis, because the Engel index is one way to reflect the standard of living of a person or group of people. The results of the analysis using the Engel Index obtained a figure of 28.52%, this means that the total income of fishermen who own fishing rods is not much, even less than half of their income is used for food needs only. It can be concluded that the level of welfare of fishermen who own fishing rods is classified as good / high because more than half of their income for food needs, namely 71.47%, is used for non-food needs. This means that their lives in the house already have other facilities, such as having a television in addition to children who are well schooled. This is greatly supported by the role of fishermen's wives in working and being able to provide economic support for the family. Keywords: Standard of Living, Women's Empowerment, Hand Fishing Abstrak Tujuan khusus dalam penelitian ini, yaitu : Mengidentifikasikan dan menjelaskan dengan cermat taraf hidup keluarga nelayan pancing berbasis pemberdayaan wanita/ibu rumah tangga di Desa Tateli Dua Kecamatan Mandolang Kabupaten Minahasa. 1. Metode dalam penelitian ini dipakai metode sensus. 2 Teknik Pengumpulan Data Data yang dikumpulkan melalui dua sumber yaitu data primer dan data sekunder. Data primer adalah data yang langsung diperoleh melalui wawancara langsung di loakasi penelitian, pengisian kuisioner. 3 Metode Analisis Data Analisis data hasil penelitian dibedakan dalam dua macam, yaitu analisis kuantitatif dan analisis kualitatif. Analisis Indeks Engel, karena indeks Engel merupakan salah satu cara untuk mencerminkan taraf hidup seseorang atau sekelompok orang. Hasil analisis dengan menggunakan Indeks Engel diperoleh angka 28,52 %, ini berarti bahwa total pendapatan nelayan pemilik pancing tidak banyak bahkan tidak sampai separuh pendapatannya yang digunakan kebutuhan makanan saja. Hal ini dapat disimpulkan bahwa tingkat kesejahteraan nelayan pemilik pancing tergolong baik/tinggi karena lebih dari separuh pendapatannya kebutuhan pangan saja yaitu sebesar 71,47% digunakan untuk kebutuhan non pangan. Ini berarti kehidupan mereka di dalam rumah sudah ada fasilitas yang lain misalnya memiliki televisi disamping anak-anak yang disekolahkan dengan baik. Hal ini sangat ditunjang oleh peranan istri nelayan dalam ikut bekerja dan bisa memberikan dukungan ekonomi bagi keluarga. Kata kunci : Taraf Hidup, Pemberdayaan Wanita, Pancing Ulur.